2,3,5,4'-Tetrahydroxy-stilbene-2-O-beta-d-glucoside induces autophagy-mediated apoptosis in hepatocytes by upregulating miR-122 and inhibiting the PI3K/Akt/mTOR pathway: implications for its hepatotoxicity - Lei Yang; Wei Xing; Wang-Zhong Xiao; Lin Tang; Lu Wang; Meng-Jiao Liu; Bing Dai (Taylor & Francis Group, 2020)
Context The potential hepatotoxicity of Polygoni Multiflori Radix (PMR) has attracted much attention, but the specific mechanism of inducing hepatotoxicity is still unclear due to the complexity of its components. Objective This study investigated the specific mechanism by which 2,3,5,4'-tetrahydroxy-stilbene-2-O-β-d-glucoside (TSG) regulates hepatotoxicity. Materials and methods The toxic effects of TSG (10, 100, 1000 μg/mL) on WRL-68 cells were examined using MTT, flow cytometry, and LDH assay after 24 h of incubation. Untreated cells served as the control. Gene and protein expression levels were determined by quantitative real-time PCR and Western blot, respectively. Immunofluorescence analysis was conducted to investigate the expression of light chain 3 (LC3). Luciferase activity assay was used to assess the targeted regulation of RUNX1 by miR-122. Results The half maximal inhibitory concentration (IC50) of TSG in WRL-68 cells was calculated as 1198.62 μg/mL. TSG (1000 μg/mL) inhibited cell viability and LDH activity and promoted WRL-68 cell apoptosis by inducing autophagy. Subsequent findings showed that TSG induced autophagy and promoted apoptosis in WRL-68 cells by downregulating the levels of p-PI3K, p-Akt, and p-mTOR proteins, while RUNX1 overexpression rescued this inhibition. Additionally, the effect of TSG on hepatocyte apoptosis was reversed by miR-122 knockdown. Furthermore, bioinformatics and dual luciferase reporter assay results indicated that miR-122 targeted RUNX1. Discussion and conclusions Our data demonstrate for the first time that TSG regulates hepatotoxicity, possibly by upregulating miR-122 and inhibiting the RUNX1-mediated PI3K/Akt/mTOR pathway to promote autophagy and induce hepatocyte apoptosis. Further in vivo research is necessary to verify our conclusion.